PENERAPAN HANDOUT VISUAL BERBANTUAN MEDIA CULTURE CARD UPAYA PENINGKATAN PEMAHAMAN MATERI KEBERAGAMAN BUDAYA INDONESIA SISWA KELAS IV SDN JATISARI SEMARANG - Ula, Khurotul; Dewi Purwati, Panca (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning that is fixated on textbooks and does not utilize innovative teaching materials and learning media impacts the weak understanding of Indonesian cultural diversity material for fourth-grade students of Jatisari Elementary School. Indonesian diversity material is material that requires the ability to understand, remember, and memorize, so it needs to be supported by innovative teaching materials and visual media to help students understand the material more easily and arouse student interest. This study aims to describe the steps of implementing visual handouts of Indonesian cultural diversity assisted by culture card media and to test its effectiveness in improving the ability to understand Indonesian cultural diversity material for fourth-grade students of Jatisari Elementary School. The research method used is a mixed method that collects qualitative and quantitative data simultaneously. The qualitative method used is descriptive qualitative to describe the steps of implementing visual handouts assisted by culture card media in the learning process of Indonesian cultural diversity material. The quantitative method used is a pretest-posttest one-group design whose data is obtained from the pretest and post-test scores. The results showed an increase in the average pretest to the post-test score, which was 57.2 to 83.1 and the results of the N-Gain test obtained a value of 0.61 with moderate criteria. Based on these results, it can be concluded that the application of visual handouts assisted by culture card media is quite effective in improving the understanding of Indonesian cultural diversity in grade IV students of Jatisari Elementary School.